2021
DOI: 10.1007/s11663-021-02091-z
|View full text |Cite
|
Sign up to set email alerts
|

The Spontaneous Emulsification of Entrained Inclusions During Casting of High Aluminum Steels

Abstract: Mold slag entrainment during the continuous casting process presents a late stage source of non-metallic inclusions (NMI) with a high likelihood of ending up in the final product. The reaction between the entrained slag phase and surrounding liquid steel in the continuous casting mold affects the inclusion morphology and properties. However, there is a lack of information on the kinetics of the NMI-steel reaction. A novel approach, utilizing controlled synthetic inclusion/metal samples, has been developed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This test method provided unique information on the inclusion-steel reaction behaviour, where it was observed that the inclusion's surface area increased by a factor of 13 times its original size when the reaction occurred due to spontaneous emulsification occurring. Further information on this phenomena can be found in our published work (Raviraj et al, 2021).…”
Section: Successes and Shortcomings Of The Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…This test method provided unique information on the inclusion-steel reaction behaviour, where it was observed that the inclusion's surface area increased by a factor of 13 times its original size when the reaction occurred due to spontaneous emulsification occurring. Further information on this phenomena can be found in our published work (Raviraj et al, 2021).…”
Section: Successes and Shortcomings Of The Methodsmentioning
confidence: 89%
“…The principles of operation for the HT-CLSM are described in (Raviraj et al, 2021) and the equipment can be used for a variety of experiments with direct observation of the sample. In this work the HT-CLSM is used for two types of tests, described in Experimental Techniques with the general principles covered here (and described in more detail in Samples of a maximum size of 1 cm diameter are placed into an alumina crucible which is then loaded into the HT-CLSM chamber.…”
Section: High-temperature Confocal Laser Scanning Microscopementioning
confidence: 99%
See 1 more Smart Citation